Decarbonizing the food and beverages industry: A critical and systematic review of developments, sociotechnical systems and policy options - Sovacool, Benjamin (2021)
From farm to fork, food and beverage consumption can have significant negative impacts on energy consumption, water consumption, climate change, and other environmental subsystems. This paper presents a comprehensive, critical and systematic review of more than 350,000 sources of evidence, and a short list of 701 studies, on the topic of greenhouse gas emissions from the food and beverage industry. Utilizing a sociotechnical lens that examines food supply and agriculture, manufacturing, retail and distribution, and consumption and use, the review identifies the most carbon-intensive processes in the industry, as well as the corresponding energy and carbon “footprints”. It discusses multiple current and emerging options and practices for decarbonization, including 78 potentially transformative technologies. It examines the benefits to sector decarbonization—including energy and carbon savings, cost savings, and other co-benefits related to sustainability or health—as well as barriers across financial and economic, institutional and managerial, and behavioral and consumer dimensions. It lastly discusses how financing, business models, and policy can be harnessed to help overcome these barriers, and identifies a set of research gaps.